Multi-ancestry meta-analysis of genome-wide association studies discovers 67 new loci associated with chronic back pain - Ian B. Stanaway; Pradeep Suri; Niloofar Afari; Daniel Dochtermann; Armand Gerstenberger; Saiju Pyarajan; Eric J. Roseen; Million Veteran Program; Marianna Gasperi (Nature Communications)
Abstract This multi-ancestry meta-analysis of genome-wide association studies (GWAS) investigated the genetic factors underlying chronic back pain (CBP) in a sample from the Million Veteran Program comprised of 553,601 Veterans of African (19.2%), European (72.6%), and Hispanic (8.2%) ancestry. The results revealed novel (N = 67) and known (N = 20) genome-wide significant loci associated with CBP, with 43 independent variants replicating in a non-overlapping contemporary meta-GWAS of the spinal pain dorsalgia phenotype. The most significant novel variant was rs12533005 (chr7:114416000, p = 1.61 × 10−20, OR = 0.96 (95% CI: 0.95–0.97), EA = C, EAF = 0.39), in an intron of the FOXP2 gene. In silico functional characterization revealed enrichment in brain and pituitary tissues. Mendelian randomization analysis of 62 variants for CBP-MVP revealed 48 with causal links to dorsalgia. Notably, four genes (INPP5B, DRD2, HTT, SLC30A6) associated with these variants are targets of existing drugs. Our findings more than double the number of previously reported genetic predictors across all spinal pain phenotypes.